The Small GTP-Binding Protein Rho Potentiates AP-1 Transcription in T Cells - Chang, Jin-Hong (American Society for Microbiology, 1998)
The Rho family of small GTP-binding proteins is involved in the regulation of cytoskeletal structure, gene transcription, specific cell fate development, and transformation. We demonstrate in this report that overexpression of an activated form of Rho enhances AP-1 activity in Jurkat T cells in the presence of phorbol myristate acetate (PMA), but activated Rho (V14Rho) has little or no effect on NFAT, Oct-1, and NF-κB enhancer element activities under similar conditions. Overexpression of a V14Rho construct incapable of membrane localization (CAAX deleted) abolishes PMA-induced AP-1 transcriptional activation. The effect of Rho on AP-1 is independent of the mitogen-activated protein kinase pathway, as a dominant-negative MEK and a MEK inhibitor (PD98059) did not affect Rho-induced AP-1 activity. V14Rho binds strongly to protein kinase Cα (PKCα) in vivo; however, deletion of the CAAX site on V14Rho severely diminished this association. Evidence for a role for PKCα as an effector of Rho was obtained by the observation that coexpression of the N-terminal domain of PKCα blocked the effects of activated Rho plus PMA on AP-1 transcriptional activity. These data suggest that Rho potentiates AP-1 transcription during T-cell activation.